Digital technology’s impact on senior high school students’ religious attitudes - Wibowo, A. M.; Laili Noviani, Nur; Muzayanah, Umi; Istiyani, Dwi; Muawanah, Siti; Mudis Taruna, Mulyani; Wahab, Wahab; Muntakhib, Ahmad; Eko Atmanto, Nugroho (Institute of Advanced Engineering and Science, 2025)
The advancement of technology has revolutionized student learning, shifting from traditional textbooks to digital tools, reducing teacher-student interaction, and impacting students’ perspectives and attitudes. Students with extreme religious views sometimes rely more on digital resources than traditional ones. This study examines: i) the effect of learning resources on students’ religious attitudes; ii) the influence of social status on their attitudes; iii) the relationship between students’ motivation for religious learning and their attitudes; and iv) the interaction between diverse learning resources and social status on students’ religious attitudes. Using quantitative methods and multiple regression analysis on data from 1,020 students in Central Java, Indonesia, and employing partial least square (PLS) modeling, the study explores the influence of religious resources, social class, and motivation on students’ views. The findings show that diverse learning resources significantly foster moderate religious attitudes, with social class also playing a pivotal role. Notably, students’ motivation for religious learning mediates the relationship between learning resources and social class in shaping religious attitudes. This study contributes to educational theory by highlighting the role of learning resources in shaping outcomes, social theory by demonstrating how socioeconomic factors influence religious attitudes, and religious theory by exploring the role of digital tools in shaping religious views. These insights provide practical implications for educators in designing effective religious education strategies and promoting moderation in the digital era while emphasizing the importance of face-to-face learning for meaningful dialogue.